Political communication and economic reform: The use of consumerist frames in Brazil, 1985-2005 - Sybil Rhodes (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2012)
An enduring puzzle for scholars of Latin American policy reform asks how policy makers push through reforms with short term costs but long term benefits in mass democracies. Many answers have been given, including international pressures, cultural and ideational factors, the nature of political institutions, deceptive policy switches, and the power of concentrated interests. These explanations and others disregard the question of how policy elites attempt to build mass legitimacy for reforms through political communication strategies such as framing and agenda setting. In the case of Brazil, I argue, policy elites and media messages framed arguments about reform policies in terms of the consumer interest in competitive economic markets. I present an analysis of newspaper coverage of consumer issues in Brazil to show that attention to the critical competition frame increased during the first reform attempts under President Fernando Collor de Melo and, more clearly, during the main period of reforms under Fernando Henrique Cardoso.
Keywords: 330